KEWENANGAN PEMERINTAH DAERAH DALAM PENGATURAN LARANGAN PENAHANAN ATAU PENYIMPANAN DOKUMEN ASLI PEKERJA OLEH PENGUSAHA - Sinda Eria Ayuni; Sudarsono Sudarsono; Tunggul Anshari (Legality : Jurnal Ilmiah Hukum, 2019)
The prohibition or recommendation for the detention of workers 'original documents is not clearly stipulated in the labor law so that some employers detain or retain workers' original documents to be made to bind workers. This is permissible if it becomes an agreement between workers and employers, but of course there will be some risks borne by workers if the original documents are guaranteed. In this case a clear and definite rule is needed regarding the prohibition of hold or save of original documents of workers by employers as an effort to protect workers. The government has the authority to make regulations that can protect workers from arbitrary rules made by employers